Non-communicable diseases among low income adults in rural coastal communities in Eastern Sabah, Malaysia - Hazriani Harris; Yasmin B. H. Ooi; Jau-Shya Lee; Patricia Matanjun (BMC, 2019)
Abstract Background Rural coastal communities in Sabah are still overly represented in the hardcore poor economic status. The aim of this study was to determine the prevalence of hypertension, diabetes mellitus and hypercholesterolemia among adults, in relation to economic status. Methods A cross-sectional study using stratified random sampling was conducted in seven coastal villages in Semporna, Sabah: Kabogan Laut, Salimbangun, Pekalangan, Pokas, Tampi-Tampi Timbayan, Sum Sum and Selinggit. Socio-demographic data were obtained via interviewer administered questionnaires in Sabah Malay creole. Anthropometric measurements, blood pressure, fasting blood glucose and blood lipids were obtained. Results A total of 330 adults (133 males, 197 females) completed the study. Mean age was 43.7 ± 15.8 years. Most participants (87%) were living below the Poverty Line Income. Median per capita household income was RM83.33/month (≈ USD20/month). The number of newly diagnosed cases of hypercholesterolemia was 40.6%, diabetes mellitus was 5.8%, and hypertension was 24.5%. Adults from the hardcore poor economic status (household income ≤RM760/month (≈USD183/month) were the most represented in those who did not have a blood pressure, blood sugar and blood lipids check in the 12 months preceding the study (Χ2, p < 0.01). Adults from hardcore poor economic status were also the most represented in undiagnosed hypertension and uncontrolled blood pressure among those diagnosed (Χ2, p = 0.013). Among diabetics from the hardcore poor group, the undiagnosed fasting blood glucose was 11.2 ± 4.5 compared to 5.1 ± 0.6 mmol/L for diagnosed diabetics (p < 0.001). Among hypercholesterolemics from the hardcore poor group, total cholesterol and LDL cholesterol values were significantly higher in the undiagnosed group compared to the diagnosed group (p < 0.001). Conclusion Many people in this rural coastal community were unaware that they had high cholesterol level (40.6%) and elevated blood pressure (24.5%). Routine health check is not common among low income adults in rural coastal communities in Semporna. The findings suggest public health initiatives should emphasize access to and the necessity of routine health checks for those aged 40 years.